Toxity Test Of Primary And Secondary Metabolite Extracts On Caulerpasp. Which Is Cultivated By The Community Of The District Takalar - Andis Sugrani; Nuramaniyah Taufiq; Qurrata Khusnul Khatimah; Valen Tiwa Patanduk; Sri Wahyuni Pakayya (International Journal of Health and Pharmaceutical (IJHP), 2024)
Lawi-lawi (Caulerpa sp) has economic value for some coastal communities who cultivate it. Apart from having the opportunity to be exported abroad as a complement to processed seafood, it turns out that lawi-lawi can also be used as an antidote to cancer or malignant diseases. This research is about the level of toxicity of the seaweed extract fraction (Caulerpa sp) on Artemia salina Leach larvae, method while for screening anticancer activity used the Brine Shrimp Lethality Test (BSLT) method. In methanol extract Caulerpa sp based on the results of toxicity test measurements using the BSLT method, it is included in the toxic category. Primary extract In Caulerpa sp based on the results of toxicity test measurements using the BSLT method, it is included in the very toxic category.